Construction of Biocompatible Dual-Drug Loaded Complicated Nanoparticles for in vivo Improvement of Synergistic Chemotherapy in Esophageal Cancer - Zhan, Wenhua; Li, Hanrui; Guo, Yingying; Du, Getao; Wu, Yayan; Zhang, Dexin (Frontiers in Oncology, 2020)
Combination chemotherapy is a routine treatment for esophageal cancer, but some shortcomings, such as drug toxicity and side effects, greatly limit the clinical application of combination therapy. To overcome these shortcomings, we have developed a mesoporous silica nanoparticle system that was used to load doxorubicin and β-elemene. β-elemene was encapsulated in the pore of mesoporous silica nanoparticle and doxorubicin was electrostatically adsorbed on the surface of mesoporous silica nanoparticle by hyaluronic acid to construct dual drugs synergistic nanoparticles (bMED NPs, ~77.15 nm). In vitro studies demonstrated that bMED NPs had a good treatment effect in esophageal cancer cell lines. In vivo fluorescence imaging results demonstrated that bMED NPs could accumulate in tumor sites and achieve in vivo long-term circulation and continuous drug release. In addition, bMED NPs exhibited significant antitumor effects in the esophageal cancer mouse model, which may provide a great platform for esophageal cancer chemotherapy.